Cardioprotective Mechanism of Chemical Constituents of Medicinal Plant: A Brief Review - Kosanam , Sreya; Pasupula , Rajeshwari (Challenges and Advances in Pharmaceutical Research Vol. 2, 2022)
Plants are major source of human living. Since the beginning of the era plants have been used for medicinal purposes. There is an urgent need to investigate the mechanisms of chemical constituents in plants, particularly saponins and cardiac glycosides, because of their ability to save damaged cells in cardiac muscle. Articles describing the cardioprotective mechanism of medicinal plants were found by searching databases such as Google Scholar, Medline, PubMed, and the Directory of Open Access Journals. Saponin, flavonoids, glycoside, steroid, alkaloids, tannin, phenol, phlobatanin, terpenoids, and anthraquinone are chemical constituents in plants that improve cardioprotective activity and reduce cardiac abnormalities. The current review article provides information on the use of medicinal plants, specifically against cardiac diseases, as well as a study of molecules/phytoconstituents as plant secondary metabolites for their cardioprotective potential. The main objective of this review chemical constituents in herbal or traditional plants can be lifesaving in chronic heart diseases.